Respuesta :
-3x + 5y = -2
2x - 2y = 1
2x = 1 + 2y
x = 1/2 + y
Substitute x into the first equation.
-3(1/2 + y) + 5y = -2
3/2 - 3y + 5y = -2
3/2 + 2y = -2
2y = -2 + 3/2
2y = -1/2
y = (-1/2)/2
y = -1/4
So finish solving for x.
x = 1/2 + y
x = 1/2 - 1/4
x = 1/4
So x = 1/4 and y = -1/4
2x - 2y = 1
2x = 1 + 2y
x = 1/2 + y
Substitute x into the first equation.
-3(1/2 + y) + 5y = -2
3/2 - 3y + 5y = -2
3/2 + 2y = -2
2y = -2 + 3/2
2y = -1/2
y = (-1/2)/2
y = -1/4
So finish solving for x.
x = 1/2 + y
x = 1/2 - 1/4
x = 1/4
So x = 1/4 and y = -1/4